Cloning and characterization of bovine growth hormone (BGH) gene from local gaur(Seladang) - Jusoh, Abdul Rashid (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Bovine growth honnone gene (bGH) is well know among the scientist all over the world. Various types of bGH gene has been publish from various bovine species. Expression of that sequence has produced a valuable protein that is known as bovine growth hormone. These hormone play important role in regulated the differentiation, growth and metabolism of cattle. Has been proven that, this hormone play important role in increasing the production of milk. In searching full information about that gene, many bGH sequence has been explore in different bovine species However the sequence of bGH gene from Bos gaurus hubbacki (local Malaysian gaur) still not explore yet. To grab these opportunity my supervisor with collaboration of Seladang Conservation Centre has proposed these study. In this study we try to clone and characterize bGH gene from genomic DNA. The genomic DNA was extracted from gaur tissue using phenol chloroform method proposed by Maniatis et al. (1989). The bGH gene has been amplified using polymerase chain reaction. Amplified product then has been further clone into T A Cloning vector. The recombinant plasmid has been transfonned into E.coli DH5a. The cloned DNA finally has been submitted for sequencing and sequence analysis of the gene has been carried out. This study reveals that, bGH gene has been successful cloned from genomic DNA of local gaur. The size of the cloned gene is 1208 bp and has high similarity with bGH gene from other bovine species reported in GenBank.